The Effect of Drying Methods on the Physicochemical Characteristics of Curly Red Chili (Capsicum annuum L.) - Birgitta Allison Kesuma; Ika Yohanna Pratiwi; Yohannes Somawiharja (Journal of Agri-Food Science and Technology, 2025)
Curly red chili has high nutritional content, which includes capsaicinoids, vitamin C, carotenoids, and antioxidant compounds. However, their high moisture content renders them perishable. During peak harvest seasons, prices for chili significantly decrease, while they tend to rise in colder months. Inefficient postharvest technologies contribute to substantial waste due to damage. Effective postharvest processing, such as drying, mitigates these challenges by reducing moisture content and extending shelf life. Various drying methods, including food dehydration, oven, vacuum frying, and freeze drying, have distinct advantages and disadvantages. Comparative studies have been conducted on these methods specifically for curly red chili. This study contributes to evaluating the effects of different drying methods on the color, moisture content, vitamin C content, and capsaicin concentration of curly red chili (Capsicum annuum L.) in order to determine the most effective method for preserving its nutritional and physicochemical qualities. The results indicate that the drying method significantly influences the physicochemical properties of curly red chili. Among the methods tested, freeze-drying emerged as the most effective, based on the color of 66.69 ± 2.25, moisture content of 3.81%, and vitamin C of 94.34 mg/100g. The optimal treatment yielded a spiciness level of 16504.71 SHU with a capsaicinoid content of 1100.32 mcg/g. Further research is needed to explore how moisture content affects capsaicin levels in curly red chili.